2018
DOI: 10.1155/2018/5076259
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the Delivery of Inhaled Medication for Respiratory Patients: The Role of Valved Holding Chambers

Abstract: Valved holding chambers (VHCs) have been used with pressurized metered-dose inhalers since the early 1980s. They have been shown to increase fine particle delivery to the lungs, decrease oropharyngeal deposition, and reduce side effects such as throat irritation, dysphonia, and oral candidiasis that are common with use of pressurized metered-dose inhalers (pMDIs) alone. VHCs act as aerosol reservoirs, allowing the user to actuate the pMDI device and then inhale the medication in a two-step process that helps u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 48 publications
1
11
0
8
Order By: Relevance
“…Aerochamber® was used as a reference of commercial VHCs in 4 out of the 6 trials. In this current study, we also used Aerochamber® as a reference not only because it is available in our country but it also has considerably scientific data especially in young children 6,25,26 . The findings of our study are consistent with those previously reported.…”
Section: Discussionsupporting
confidence: 91%
“…Aerochamber® was used as a reference of commercial VHCs in 4 out of the 6 trials. In this current study, we also used Aerochamber® as a reference not only because it is available in our country but it also has considerably scientific data especially in young children 6,25,26 . The findings of our study are consistent with those previously reported.…”
Section: Discussionsupporting
confidence: 91%
“…Generally, pressurized metered-dose inhalers (pMDIs) are the most frequently used devises worldwide due to their acceptable cost, effectiveness, and simple technique. 8 Although inhaled medications are considered the optimal route and gold standard for the treatment of COPD, their delivery to the site of action can be challenging. In fact, most patients are not able to use the devices correctly without training and some cannot use them properly despite education.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, most patients are not able to use the devices correctly without training and some cannot use them properly despite education. 7 , 8 It has been proposed that patients’ technique of using devices can lead to a significant difference in clinical response even between pMDIs and dry powder inhalers (DPIs) despite their similar efficacy in correct use. 9 In a systematic review of the studies published between 1975 and 2014, a high prevalence of inappropriate device use among patients with pulmonary disorders was noted.…”
Section: Introductionmentioning
confidence: 99%
“…McIvor et al [1] recently suggested that regulatory authorities (e.g., US Food and Drug Administration (FDA), Health Canada, and Japan's Pharmaceuticals and Medical Devices Agency) should harmonize and follow the European Medicines Agency (EMA) recommendation that valved holding chambers (VHCs) are not interchangeable.…”
mentioning
confidence: 99%
“…In our opinion, using only laboratory criteria to determine superiority of any MDI + VHC combination over another fails to take into account important “real-world” device and patient-related clinical issues. These are determined by pMDI and VHC/mask design features that individually or in combination will surely have an effect that is equal to or greater than the recent laboratory-demonstrated differences in various MDI + VHC combinations [2] that, as a result, have led to totally unwarranted clinical conclusions [1].…”
mentioning
confidence: 99%